Adapting the Utilization-Focused Approach for Teacher Evaluation - Lindsay A. Noakes (Journal of MultiDisciplinary Evaluation, 2009)
Mandated teacher evaluations are of little use to educators for a variety of reasons, including lack of reliability and validity of evaluation instruments and methods, failure of evaluation systems to adhere to the Personnel Evaluation Standards (Joint Committee, 2008), and the inherent bias in using classroom observations as a method of evaluating teachers. As a result, teacher evaluations fail to improve teaching or impact student learning. This paper suggests that the utility, and ultimately the impact, of teacher evaluations can be improved by adapting the utilization-focused approach to teacher evaluations. Specific suggestions for implementing the Utilization-focused Evaluation Checklist (Patton, 2008) are also provided.